Application of magnetic N-doped carbon nanotubes in solid-phase extraction of trace bisphenols from fruit juices. (15th December 2018) - Jiang, Hai-Long; Lin, Yun-Liang; Li, Na; Wang, Zhi-Wei; Liu, Meng; Zhao, Ru-Song; Lin, Jin-Ming
Highlights: Magnetic nitrogen doped carbon nanotubes were firstly applied in food analysis. Adsorption conditions were optimized by response surface methodology. The method was effective to determine trace bisphenols in fruit juices. The adsorption mechanisms was discussed for further development of the method. Abstract: Magnetic N -doped carbon nanotubes were firstly applied as adsorbent in food analysis for pre-concentration of bisphenols in fruit juices followed by ultra-high performance liquid chromatography-tandem mass spectrometry determination. The magnetic nanoparticles were characterized by X-ray diffraction, infrared spectroscopy, scanning electron microscopy and vibrating sample magnetometer. The adsorption conditions were further optimized by response surface methodology. Under optimal conditions, the method provided good linearity with correlation coefficient ( r  ≥ 0.9979), excellent intermediate precisions (2.71–5.91%, n = 3), low limits of detection (LODs) ranging from 0.43 to 2.47 ng L −1, and satisfying recoveries of three juice samples (between 90.6% and 101%).